From ancient crop to modern superfood: Exploring the history, diversity, characteristics, technological applications, and culinary uses of Peruvian fava beans - Salvador Reyes, Rebeca (2023)
The search for plant-based superfoods has shown that many regional populations already have these foods in their diet, with significant potential for production and marketing. This critical review intends to show the history, diversity, characteristics, and uses, emphasizing their significance in traditional diets and potential in the food industry of Peruvian fava beans. As a valuable plant-based protein source, fava beans offer essential micronutrients and have diverse culinary applications. Innovative food industry applications include plant-based meat alternatives, fortified gluten-free products, and a natural color, protein, and fiber source in extruded foods. Key studies have highlighted the successful incorporation of fava beans into various food products, improving their nutritional properties, though some studies also point to limitations in their sensory acceptance. Further research is needed to understand the bioactive components, health effects, and techno-functional characteristics of beans. Challenges facing cultivating and consuming fava beans in Peru include adapting to climate change, enhancing productivity and quality, and promoting consumption and added value. Addressing these challenges involves developing climate-resilient varieties, optimizing agricultural practices, and providing access to resources and financing. In conclusion, this review highlights the promising prospects of Peruvian fava beans as a sustainable, nutritionally rich, and versatile ingredient in the food industry. By harnessing their potential and overcoming challenges, Peruvian fava beans can transition from an ancient crop to a modern superfood, inspiring a global shift towards sustainable and nutritionally balanced diets, aiding the fight against malnutrition, and enriching culinary traditions worldwide.